Hakekat Dan Aplikasi Kaidah Fiqih Tafriq Al-Halal ‘An Al-Haram (Idza Ijtama’ Al-Halal Wa Al-Haram Ghuliba Al-Haram) - Hudzaifah Achmad Qotadah (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2023)
This article aims to discuss the principles of fiqhiyyah at-tafriq baina al-halal wal haram (separation between something halal and haram). The rule that is the subject of study is the rule, namely the rule "idza ijtama' al-halal wa al-haram ghuliba al-haram" (if it is mixed between what is lawful and what is unlawful, then the mix is considered unlawful). This research is a qualitative type research based on library research which is then analyzed descriptively. The results of the study show that the separation between halal and haram in Islam is very important because each has different implications and consequences so that Muslims are expected to always try to understand and practice the principles of tafriq al halal an al haram in all kinds of life activities.